Análise da expressão gênica diferencial- na divisão de trabalho em Apis Mellifera Linnaeus, 1758 (hymenoptera. Apidae) por Ddrt-pcr - Oliveira Junior, Waldesse Piragé de (1999)
Apis mellifera bees have been around for 100 million years, and their importance to humans began to be defined in 2,400 BC with the start of beekeeping in ancient Egypt. Today, bees are found in many environments except the Sahara Desert and the North and South Pole glaciers. The Apis colony is one of nature's most remarkable achievements as it is extremely organized and is grounded in a well-defined division of labor.Several studies have been done to clarify this division, however, little is known about its molecular regulation mechanisms. The Differential Display Reverse Transcriptase - Polymerase Chain Reaction (DDRT-PCR) technique, described by Liang in 1992, is today the most efficient for identifying and isolating differentially expressed genes under a given condition. Thus, this work aims to optimize the total RNA extraction of Apis mellifera, as well as to optimize DDRT-PCR with silver nitrate staining, regarding the differential gene expression of this species in its division of labor. In this study, sixty hours of observations were performed to characterize the division of labor in an observation hive. At the same time, samples of bees with 1, 5, 10, 15, 20, 25 and 30 days of adult life were collected for later extraction of total RNA. Reverse transcription was then performed and then cDNA amplification was performed by combining an oligo d (T) primer with six arbitrary OPA primers (10 bp). Thus, several tests were performed to obtain the complete optimization of the technique. In addition, it was optimized using non-radioactive silver nitrate labeling. The The results found showed polymorphisms that varied between age groups for each combination of primers. The OPA 08, OPA17 and OPA18 primers allowed to detect a larger number of fragments than the others (OPAs 12, 14 and 16). These fragments were mostly between 100 and 900 bp and several of them were present at specific ages. Of the differentiated bands, detected by the presence or absence at a certain age or by their variation in intensity, the following stand out: three fragments (100, 200 and 300 bp) that may be related to the nursing or cleaning function (12 to 5 = day ); one with about 350 bp present only on the 15th day, which may indicate association with wax production and 600 Db n ~ Zii + imn present at all ages, honeycomb construction and one last of P r, in the age of 52 to 152 days, may also have higher intensity from the 5th to the 15th day, may also have relationship with the building of combs. This showed that the technique was successfully performed and silver staining can be adopted as an alternative to radioactive labeling in DDRT-PCR.